The Organization of Military Courts in the Interwar Period in the Republic of Poland - Ćwikła, Adam (PRAWO i WIĘŹ, 2024)
The military judiciary in the interwar period in the Republic of Poland faced many problems, especially those that originated from the process of creating its own existence after Poland regained independence. The first significant obstacle in the legal system of the Republic was the application of various laws of the former occupiers on its territory. In addition, the young state had no guarantees regarding the security of its borders and therefore maintained a large army. Thus, the question of the justification for maintaining a separate justice system in the army did not find too many supporters. Despite the short period of the Republic’s existence on the maps of Europe, interrupted by the outbreak of World War II, it did not prevent significant changes in the scope of military judiciary in Poland.